STEREOLOGICAL CHALLENGES WHEN WORKING WITH HEART MUSCLE FIBRES - Brüel, Annemarie (Image Analysis and Stereology, 2011)
This contribution is based on a series of studies, where stereological methods were applied to hearts from rats treated with growth hormone. A method to estimate the total number of cardiac myocytes is described and, furthermore, length estimates of heart muscle fibres are discussed.